Spontaneous Coronary Artery Dissection: Mechanisms, Diagnosis and Management - Garcia-Guimarães, Marcos (Eur Cardiol, 2020)
Spontaneous coronary artery dissection (SCAD) is a relatively infrequent cause of acute coronary syndrome that usually affects young to middle-aged women. Mainly because of its low prevalence, until recently, most of the evidence on this condition was derived from case reports and small series. Over the last 5 years, more robust evidence has become available from larger retrospective and prospective cohorts of patients with SCAD. The increase in knowledge and recognition of this entity has led to the publication of expert consensus on both sides of the Atlantic. However, new data are continuously accumulating from larger cohorts of patients with SCAD, bringing new light to this little-understood condition. The aim of this article is to update the knowledge on SCAD, including new information from recent studies published since the consensus documents from the European Society of Cardiology and the American Heart Association.